Pengaruh Stres Kerja dan Motivasi Kerja terhadap Kinerja pada Anggota Yanma Sat Brimob Polda Jateng - Assyifa Salsabila; Hardani Widhiastuti; Rusmalia Dewi (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to examine and analyze the effect of work stress and work motivation on employee performance. The research was conducted in an elite unit of the Indonesian National Police (Polri) in Central Java, namely Yanma Sat Brimob Polda Jawa Tengah. The population consisted of 60 members, and a saturated sampling technique was applied, involving all members as respondents. Data were collected through structured questionnaires and analyzed using a quantitative approach based on Partial Least Squares Structural Equation Modeling (PLS-SEM). Data quality testing included validity and reliability tests, followed by coefficient of determination (R²), effect size (F²), and hypothesis testing using the t-test. The analysis was conducted using SmartPLS version 4 for Windows. The results indicate that work stress and work motivation simultaneously have a substantial influence on performance, with a combined explanatory power of 71 percent. Partially, both variables show a statistically significant effect on performance. However, the findings reveal that work stress in the context of Yanma Sat Brimob functions as a hindrance stressor, which tends to reduce performance effectiveness when not properly managed, rather than as a challenge stressor that enhances alertness or adaptive performance. In contrast, high work motivation consistently contributes to improved performance outcomes. These results suggest that while motivation serves as a performance-enhancing factor, unmanaged work stress acts as a performance-inhibiting factor. Therefore, organizational management within Yanma Sat Brimob Polda Jawa Tengah is expected to prioritize effective stress management strategies alongside motivational reinforcement to optimize member performance. This study provides empirical evidence that can support policy formulation and human resource management in high-risk organizational environments.